Safety and feasibility of three port procedure in laparoscopic cholecystectomy - Gupta, Vipin; Singh, Shailendra Pal; Singh, Somendra Pal; Keshari, Anil Kumar; Erry, Anil Kumar; Gupta, Poonam; Singh, Vikram; Singh, Mayank (International Surgery Journal, 2019)
Background: Laparoscopic cholecystectomy is widely accepted gold standard technique for management of cholelithiasis and has undergone many refinements including decrease in size and number of ports. Many researchers have claimed that three-port laparoscopic cholecystectomy is safe and feasible method for management of cholelithiasis but still it is not performed widely by the surgeons. Objective of our study was to assess the safety and feasibility of three-port laparoscopic cholecystectomy by comparing the various defined parameters with the standard four-port laparoscopic cholecystectomy. Methods: The study included 100 patients and was divided equally in 2 groups. Patients in Group A underwent laparoscopic cholecystectomy by three-port technique and in Group B were operated by four-port technique. Patients in both the groups were compared in terms of operative time, intra-operative complications, post-operative pain, post-operative complications and cosmesis outcome. Results: The mean operative time was similar in both groups. Intra-op and post-op complications were also similar. 3 patients in Group A needed fourth port and 1 patient in both group required conversion to open cholecystectomy. Mean pain score and requirement of parentral analgesia was found to be lower in Group A. Duration of hospital was similar in both the groups. Patients in group A had slightly better cosmetic outcome. Conclusions: Three-port laparoscopic cholecystectomy is a minimally invasive, safe and feasible technique and is not difficult to master than other advanced techniques. In experienced hands, laparoscopy cholecystectomy can be initially started with three-ports and can be converted to four-port if rarely necessary.